Β-glucans: wide-spectrum immune-balancing food-supplement-based enteric (β-WIFE) vaccine adjuvant approach to COVID-19. Issue 8 (3rd August 2021) - Ikewaki, Nobunao; Iwasaki, Masaru; Kurosawa, Gene; Rao, Kosagi-Sharaf; Lakey-Beitia, Johant; Preethy, Senthilkumar; Abraham, Samuel JK
ABSTRACT: Conventional vaccines to combat COVID-19 through different approaches are at various stages of development. The complexity of COVID-19 such as the potential mutations of the virus leading to antigenic drift and the uncertainty on the duration of the immunity induced by the vaccine have hampered the efforts to control the COVID-19 pandemic. Thus, we suggest an alternative interim treatment strategy based on biological response modifier glucans such as the Aureobasidium pullulans AFO-202-derived β-glucan, which has been reported to induce trained immunity, akin to that induced by the Bacille Calmette-Guérin vaccine, by epigenetic modifications at the central level in the bone marrow. These β-glucans act as pathogen-associated molecular patterns, activating mucosal immunity by binding with specific pathogen recognition receptors such as dectin-1 and inducing both the adaptive and innate immunity by reaching distant lymphoid organs. β-Glucans have also been used as immune adjuvants for vaccines such as the influenza vaccine. Therefore, until a conventional vaccine is widely available, an orally consumable vaccine adjuvant that acts like biosimilars, termed as the wide-spectrum immune-balancing food-supplement-based enteric (β-WIFE) vaccine adjuvant approach, with well-reported safety is worth in-depth investigation and can be considered for a clinical trial.